The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.pnpbp.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Alternative reinforcer response cost impacts cocaine choice in humans

Abstract: Cocaine use disorders are an unrelenting public health concern. Behavioral treatments reduce cocaine use by providing non-drug alternative reinforcers. The purpose of this human laboratory experiment was to determine how response cost for non-drug alternative reinforcers influenced cocaine choice. Seven cocaine-using, non-treatment-seeking subjects completed a crossover, double-blind protocol in which they first sampled doses of intranasal cocaine (5, 10, 20 or 30 mg) and completed a battery of subject-rated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 27 publications
(43 reference statements)
12
24
0
Order By: Relevance
“…As expected, manipulations in the response requirement that increased the relative price of cocaine injections vs food pellets significantly decreased cocaine choice, whereas response requirement manipulations that decreased the relative price of cocaine injections vs food pellets significantly increased cocaine choice. These results are consistent with previous nonhuman primate (Czoty et al, 2005;Nader et al, 1992;Negus, 2003;Woolverton et al, 1997) and human laboratory (Greenwald and Hursh, 2006;Stoops et al, 2012) studies examining the behavioral determinants of drug choice. Moreover, our preclinical results may be analogous to epidemiological evidence for the price sensitivity of drug consumption, which provides a rationale for both governmental policies and more targeted contingency management strategies designed to reduce drug consumption by increasing drug price or facilitating access to nondrug alternatives (Dunlop et al, 2011;Grossman, 2005;Xu and Chaloupka, 2011).…”
Section: Baseline Cocaine Choice and Effects Of Fr Manipulationssupporting
confidence: 91%
See 1 more Smart Citation
“…As expected, manipulations in the response requirement that increased the relative price of cocaine injections vs food pellets significantly decreased cocaine choice, whereas response requirement manipulations that decreased the relative price of cocaine injections vs food pellets significantly increased cocaine choice. These results are consistent with previous nonhuman primate (Czoty et al, 2005;Nader et al, 1992;Negus, 2003;Woolverton et al, 1997) and human laboratory (Greenwald and Hursh, 2006;Stoops et al, 2012) studies examining the behavioral determinants of drug choice. Moreover, our preclinical results may be analogous to epidemiological evidence for the price sensitivity of drug consumption, which provides a rationale for both governmental policies and more targeted contingency management strategies designed to reduce drug consumption by increasing drug price or facilitating access to nondrug alternatives (Dunlop et al, 2011;Grossman, 2005;Xu and Chaloupka, 2011).…”
Section: Baseline Cocaine Choice and Effects Of Fr Manipulationssupporting
confidence: 91%
“…Furthermore, both preclinical and human laboratory studies have demonstrated that cocaine choice is sensitive to manipulations in the response requirement associated with cocaine or the alternative reinforcer. For example, increases in the response requirement for cocaine or decreases in the response requirement for an alternative reinforcer can reduce cocaine choice and increase choice of the alternative (Hart et al, 2000;Nader and Woolverton, 1992;Negus, 2003;Stoops et al, 2012). Reciprocally, increases in the response requirement for the alternative reinforcer or decreases in the response requirement for cocaine can increase cocaine choice and reduce choices for the alternative (Hart et al, 2000;Nader et al, 1992;Negus, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previous human laboratory (Stoops et al, 2012) and preclinical studies (Nader and Woolverton, 1992;Negus, 2003) have demonstrated cocaine vs alternative reinforcer choice to be sensitive to response requirement manipulations. Recently, methamphetamine vs money choice in humans was also reported to be sensitive to response requirement manipulations such that a sixfold larger response requirement for money slightly, but not significantly, increased the number of methamphetamine capsules earned .…”
Section: Baseline Methamphetamine Choice and Effects Of Environmentalmentioning
confidence: 99%
“…Variables that impact choice can be examined experimentally in preclinical research using a variety of procedures (see reviews by Bergman and Paronis, 2006;Banks and Negus, 2012). For example, increasing the cost of drug or decreasing the cost of alternative nondrug reinforcers reduces drug taking in human (Stoops et al, 2012) and nonhuman primates (Nader and Woolverton, 1992;Negus, 2003). In addition to altering cost, changing other parameters of reinforcement can also significantly affect drug taking, such as increasing the time between a response and delivery of a reinforcer.…”
Section: Introductionmentioning
confidence: 99%